Long‐term effectiveness of one‐time endoscopic screening for esophageal cancer: A community‐based study in rural China. Issue 20 (30th July 2020) - Zhang, Nan; Li, Yanyan; Chang, Xuan; Lei, Fuhua; Ma, Hengmin; Liu, Jinhui; Yang, Jia; Su, Mingzhu; Sun, Xiaojie; Zhao, Deli; Sun, Qiang; Wei, Wenqiang; et al.
Abstract : Background: Evidence is required to quantify the population‐level effects of endoscopic screening for esophageal squamous cell carcinoma (ESCC). The objective of this study was to evaluate the long‐term effectiveness of 1‐time endoscopic ESCC screening in a Chinese rural population. Methods: This community‐based cohort study was based on an existing esophageal cancer screening program in Feicheng City, China. The screening group consisted of all permanent residents aged 40 to 69 years in 17 villages who were screened during 2006 through 2009, and the control group consisted of residents in another 43 villages who were not yet covered by the screening program. Residents in the remaining 511 villages were defined as the total population control. The cumulative incidence and mortality of ESCC and the observed and expected numbers of ESCC cases and deaths during the follow‐up period (2010‐2018) were calculated and compared. Results: After a 9‐year follow‐up, the screening group (n = 8460) revealed reductions of 20% (relative risk, 0.80; 95% CI, 0.66‐0.97) and 32% (relative risk, 0.68; 95% CI, 0.52‐0.89) in ESCC cumulative incidence and mortality, respectively, compared with the control group (n = 20, 468). Endoscopic screening prevented 0.41% of the population (attributable risk, 0.41%; 95% CI, 0.07%‐0.75%) from ESCC occurrence and 0.38% (attributable risk, 0.38%; 95% CI, 0.14%‐0.62%) from ESCC‐related death. In the screening group, reductions of 43% (standardized incidence ratio, 0.57; 95% CI, 0.48‐0.67) and 45% (standardized mortality ratio, 0.55; 95% CI, 0.44‐0.69) were found in the observed cumulative cases and deaths, respectively, compared with the expected cases and deaths. Conclusions: One‐time endoscopic screening was associated with a significant and consistent reduction in ESCC incidence and mortality among individuals aged 40 to 69 years in high‐risk areas. Abstract : This community‐based cohort study enables a quantitative evaluation of the long‐term impact of endoscopic screening for esophageal squamous cell carcinoma. The findings indicate that 1‐time endoscopic screening is associated with a significant and consistent reduction in esophageal squamous cell carcinoma incidence and mortality among individuals aged 40 to 69 years in high‐risk areas.